Low-dose cyclophosphamide combined with chinese herbal medicine Shuli Fenxiao formula for the treatment of intermediate-to-high risk primary membranous nephropathy - Du, Yiran; Liu, Yuning; Chen, Zhiyan; Liang, Yingnan; Li, Xia; Wang, Ying; Lv, Jie; Liu, Zhongjie; Wang, Zhen; Chen, Weihong; Liu, Qingqing; Li, Xiaowen; et al. (Frontiers in Immunology, 2025)
BackgroundAt present, the side effects of hormonal and immunosuppressant therapy for intermediate-to-high risk primary membranous nephropathy (PMN) are relatively large, and the remission rate is limited, so more safe and effective regimens are needed.MethodsThis study is a clinical prospective case series study. 31 patients were finally included. The intervention was cyclophosphamide (CTX) combined with “Shuli Fenxiao formula(SLFX formula)”, and the patients were treated for 24 weeks. The observation nodes were baseline, 2 weeks、12weeks and 24weeks after treatment.ResultsAt 12 weeks of treatment, 38.7% of patients achieved partial response. At 24 weeks of treatment, 61.3% of patients achieved partial response and 24.5% achieved complete response. All Anti-phosholipase A2 Receptor Antibody (Anti-PLA2R) seropositive patients achieved immune remission. 24-hour urine total protein quantification (24hUTP) decreased from a median of 6.1 (IQR, 4.6-8.4) g/d to 2.7 (IQR, 0.6-8.7) g/d (P<0.001). Serum albumin (ALB) increased from 27.2 ± 6.4 g/L to 31.9 ± 8.0 (P<0.05). Within 24 weeks of follow-up after discharge, no patients relapsed. During the treatment follow-up period, 6 adverse events occurred in 31 patients, 1 patient developed heart failure during the treatment period, which was not considered to be clearly associated with treatment regimen or nephrotic syndrome (NS), 3 patients were infected, and 2 patients had liver impairment.ConclusionThe results suggest that the combination of CTX and SLFX formula dramatically decreased Anti-PLA2R titers and 24hUTP levels, increased ALB in short term. The combination was safe and had few adverse effects. It has the potential to be used as a potential option for the clinical treatment of intermediate-to-high risk PMN patients, particularly for elderly patients with contraindications to corticosteroid use or those with refractory disease.International Traditional Medicine Clinical Trial Registryhttp://itmctr.ccebtcm.org.cn/, identifier ITMCTR2025000355.